THE CONCEPT OF CHILD EDUCATION IN PERSPECTIVE AL-QURAN SURAH LUQMAN VERSES 13-19 ACCORDING TO TAFSIR AL-MISBAH M. QURAISH SHIHAB - Rinto (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The purpose of this study is to determine the concept of child education in the perspective of Al-Quran surah Luqman verses 13-19, and to determine the values of child education contained in the perspective of Al-Quran surah Luqman verses 13-19. This research uses a qualitative approach by using a descriptive method (analysis technique) type of literature study (Library Research). Data collection techniques in this study were obtained from various literatures using documentation techniques. The data analysis technique used in this research is to use the method of tafsir analysis (tahlili). The results showed that: 1) The concept of Child Education in the perspective of Quran Surah Luqman Verses 13-19, namely: a) Tawhid Education is the first and main education of children about the lessons of the hereafter before knowing the lessons of the worldly to build belief in one God with loving and gentle grammar. The methods used in instilling tawhid education to children are the mau'izah method, the parable method, and the exemplary method: b) Moral Education shows three objects, namely morals to Allah SWT, morals to parents, and morals to fellow humans; c) Worship Education, namely the call for children to establish prayer after the advice of monotheism so that a child has a strong foundation of faith in life. Worship education has two directions, namely worship directed to Allah as advice to establish prayer and worship with a social dimension such as advice to prevent evil and call for virtue to humans, 2) The educational values contained in surah Luqman verses 13-19 are: a) Education of affection; b) Continuous education; c) Filial piety to both parents in terms of goodness; d) The order to establish prayer; e) Amar ma'ruf nahi munkar; f) Always have patience; g) Prohibition of being arrogant; h) Modesty in walking and talking.